An update, a correction, and an extension, of an evaluation of an illustrative Citizen's Basic Income scheme - Malcolm Torry (University of Essex, Institute for Social and Economic Research (ISER), 2018)
This is an addendum to EUROMOD working paper EM 12/17, which updates, corrects and extends the previous evaluation of an illustrative Citizen's Basic Income scheme. Debate about Citizen's Basic Income - an unconditional and nonwithdrawable income for every individual - has shifted in character. An earlier phase related to the proposal's desirability; then followed debate about its feasibility; and now attention has turned to questions of implementation. Working paper EM 12/17 operationalised characteristics of two implementation models in terms of changes that might be required in existing UK tax and benefits systems, and it evaluated the implementation methods in relation to a wider variety of indicators than previous exercises of this kind: poverty and inequality indices, tax rate rises required for revenue neutrality, household disposable income gains and losses, households' abilities to escape from means-testing, and marginal deduction rates. This addendum employs EUROMOD H1.0+ to update the evaluation of one of the two implementation methods, to make a correction in one of the marginal deduction rates, and to extend the evaluation by calculating the number of households able to escape from all means-tested benefits, and by calculating the gains and losses that would be experienced by households containing individuals with disabilities.
Keywords: C80; H53; H55; I38; R20; 330; Citizen's Basic Income; microsimulation model implementation